Image Hiding Using Discrete Cosine Transform - ايمان محمد جعفر فرح جاسم محمد (College of Education for Women, 2019)
Steganography is a mean of hiding information within a more obvious form of communication. It exploits the use of host data to hide a piece of information in such a way that it is imperceptible to human observer. The major goals of effective Steganography are High Embedding Capacity, Imperceptibility and Robustness. This paper introduces a scheme for hiding secret images that could be as much as 25% of the host image data. The proposed algorithm uses orthogonal discrete cosine transform for host image. A scaling factor (a) in frequency domain controls the quality of the stego images. Experimented results of secret image recovery after applying JPEG coding to the stego-images are included.